Studying of the effect of a dams embankment with clay core by stages on the deformations valves (Damascus University Journal for engineering sciences, 2025)
Embankment dams are complex structures that may fail due to many problems such as seepage and deformations in the dam’s body and its foundations, earthquakes, unbalanced slopes, etc. Finite Element Method (FEM) is often used in the design of earthen dams and the analysis of expected displacements, strains, and stresses of the structure caused by changeable loading or boundary conditions. Al Muzayna Dam was selected due to its touristic importance and its use for irrigation and fisheries, after observing many problems through visual examinations. These problems include a clear drop at the crest, in addition to some longitudinal cracks on the crest and the body of the dam, and grass on the back face of the dam towards the right shoulder, and also within the longitudinal cracks on the crest.The deformations were estimated during the operation period analytically using the recorded data of the geodesic points, and numerically using the SIGMA/W sub-program from the Geostudio software. The utilized software depends on the finite element method to model and simulate the deformations in the dam body and its foundations. The calculated settlements of the geodesic points were compared with the settlements calculated for 3, 5, 7 and 10 soil layers considered in construction processes.Results showed that the maximum displacement has taken place in the crest of the dam. In addition, increasing the embankment layers resulted in less deformation values. The construction layers have a limited effect on the stresses in the dam; however, that may cause a significant effect on the deformations of the dam. Keywords: Embankment dams, deformation measurements, deformation analysis Simulation, Soil layer, Settlement, staged construction.
Keywords: Embankment dams; deformation measurements; deformation analysis Simulation; Settlement; staged construction